Optimalisasi Pemanfaatan Media Pembelajaran Online Sebagai Upaya Meningkatkan Hasil Belajar Siswa di Sekolah Menengah Atas - Dodo Murtado; I Putu Agus Dharma Hita; Dhety Chusumastuti; Siti Nuridah; Akhmad Haqiqi Ma'mun; M. Daud Yahya (Journal on Education, 2023)
This study aims to evaluate the utilization of online learning media as an effort to improve student learning outcomes in high schools. The method used was literature review by collecting information from relevant sources on the research topic. The results showed that the use of online learning media has advantages such as flexibility, interactivity, and easy accessibility. However, there are also disadvantages such as limited internet access, lack of social interaction, and increased workload for teachers. The use of online learning media has a positive effect on improving student learning outcomes in high schools. Factors such as the quality of learning content, availability of facilities and infrastructure, and teacher competence in managing online learning also influence the success of online learning media implementation. Nevertheless, there are also barriers that can hinder the improvement of student learning outcomes such as lack of support from parents and the environment, as well as students' and teachers' readiness to face changes in learning methods. In conclusion, the utilization of online learning media as an effort to improve student learning outcomes in high schools during the COVID-19 pandemic has great potential. However, successful implementation requires attention to the quality of content, facilities and infrastructure, as well as the competence of teachers and students in managing online learning